Poisoning with cardiological drugs in patients hospitalized in the toxicological and cardiological department from 04/2013 to 12/2021 - Marcin Wais; Krzysztof Antoniak; Dariusz Gruca; Marlena Zając; Michał Tchórz (Kazimierz Wielki University, 2023)
Introduction and purpose: Cardiological drugs are widely used in the management of various cardiovascular diseases, such as hypertension, angina, heart failure, and arrhythmias. However, when these drugs are taken in excessive amounts or are not used as prescribed, they can become toxic and cause significant harm to the heart and other organs. Our study aims to illustrate the most frequent causes of poisoning with cardiological drugs in patients hospitalized in the toxicological and cardiological department from April 2013 to December 2021. Brief description of the state of knowledge: Poisoning with cardiological drugs is a growing concern for healthcare professionals. In 2019, cardiovascular toxins were one of the top 10 categories of poisons evaluated by medical toxicologists. Data collected from the analyzed toxicology and cardiology department include a group of 387 hospitalized patients. The largest proportion were cases intoxicated by beta-adrenoreceptor antagonists. The second most common group was poisonings by angiotensin-converting-enzyme inhibitors. A slightly lower proportion implicated poisonings caused by other, unidentified substances affecting the cardiovascular system - calcium channel blockers and other antihypertensive drugs. Conclusions: All of the data demonstrated in our study shows the importance of understanding the pharmacology, pathophysiology, and treatment strategies of poisonings caused by cardiological drugs which are one the most widely used medications worldwide.